2020
DOI: 10.3897/pharmacia.67.e58392
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro anti-diabetic activity and in-silico studies of binding energies of palmatine with alpha-amylase, alpha-glucosidase and DPP-IV enzymes

Abstract: Palmatine a protoberberine alkaloid has been previously reported to possess in vivo antidiabetic and antioxidant property. The aim of the experiment is to evaluate the in vitro antidiabetic activity and in-silico studies of the binding energies of Palmatine, acarbose, and Sitagliptin with the three enzymes of alpha-amylase, alpha-glucosidase, and dipeptidyl peptidase-IV (DPP-IV). The in vitro antidiabetic study was done by evaluating the inhibitory effect of palmatine on the activities of alpha-amylase, alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…Yet, the results from in-vitro antihyperglycemic assays present almost inverse trends in most dPREs. A probable explanation of this sort of differential binding preference may be found in previous studies which showed weak binding of metformin to α-glucosidase while acarbose exhibits strong affinity [45]. While not directly corresponding to all dPREs, docking of identified peptides from two selected samples along with control molecules show how the GP1BA and amylase binding cavity is dictated by large number of strong H-bonding and electro-attractive interactions more oriented towards metformin binding rather than the hydrophobic binding pocket of α-glucosidase optimized for quercetin, warfarin and hydrophobic peptide interactions.…”
Section: Kegg Pathway Interaction Probability Analysismentioning
confidence: 93%
“…Yet, the results from in-vitro antihyperglycemic assays present almost inverse trends in most dPREs. A probable explanation of this sort of differential binding preference may be found in previous studies which showed weak binding of metformin to α-glucosidase while acarbose exhibits strong affinity [45]. While not directly corresponding to all dPREs, docking of identified peptides from two selected samples along with control molecules show how the GP1BA and amylase binding cavity is dictated by large number of strong H-bonding and electro-attractive interactions more oriented towards metformin binding rather than the hydrophobic binding pocket of α-glucosidase optimized for quercetin, warfarin and hydrophobic peptide interactions.…”
Section: Kegg Pathway Interaction Probability Analysismentioning
confidence: 93%
“…Inhibition of adipose tissue enlargement was considered as a target to control obesity disorder. This process can be regulated by transcriptional factors like sterol regulatory element-binding protein 1 (SREBP1) (Park et al, 2019). Acetyl-CoA carboxylase played a vital role in fatty acid metabolism and was designed as a potent target for developing a new therapeutic agent in controlling obesity (Gago et al, 2011).…”
Section: Interaction Between 4-chn With Obesity-associated Proteinsmentioning
confidence: 99%
“…α-Amylase, an enzyme also called endonuclease enzyme, is engaged in the digestion of polysaccharides, whereas α-glucosidase is situated in the intestinal part which participates in absorbing oligosaccharides (Telagari and Hullatti, 2015). These enzymes were treated as key enzymes that maintained blood glucose levels by slowing the digestive process and absorption of carbohydrates and incertins (Okechukwu et al, 2020). Type 2 diabetes mellitus appears more than that of the total diabetic population, which correlates with obesity-induced insulin resistance and subsequently secreted insulin from the β-cells of the pancreas.…”
Section: Interaction Between 4-chn With Diabetes-associated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…A protoberberine alkaloid, palmatine, inhibits α-amylase and α-glucosidase activities with an IC 50 of 1.31 ± 0.27 and 9.39 ± 0.27 µM, respectively [29]. Oriciacridone C, 1,3,5trihydroxy-4-(c,c-dimethylallyl)-acridone, and oriciacridone F (Figure 3) from the stem bark of Oriciopsis glaberrima showed an α-glucosidase inhibitory activity (56 ± 5.4, 17 ± 1.0, and 34.05 ± 17 mM) [30].…”
Section: Inhibition Of Digestivementioning
confidence: 99%